Vibration energy harvesting using piezoelectric materials - Fong, Kah Jun (2014)
Vibration energy harvesting has rapidly advanced through the years, creating greater possibility of continuous and self-power supply using in wireless sensors and portable electronic devices. Because of the unique electro-mechanical coupling effect, piezoelectric materials have established their useful applications in harvesting of vibration energy in form of energy harvester.